Luminance-Chrominance Gain Equalizer Based on Bernstein Polynomials - Vanvisa Chutchavong; Ornlarp Sangaroon; Chawalit Benjangkaprasert; Kanok Janchitrapongvej (My University, 2010)
This paper presents a linear luminance-chrominance gain equalizer for correcting the linear chrominance gain distortion in the color TV transmission system. The proposed gain equalizer was implemented based on Bernstein polynomials. As it is known that the Bernstein filter has flexible parameters to adjust the circuit performance for the best results. In addition, the modulated 20T sine-squared pulse test signal is generated for testing the performance of the proposed gain equalizer, which can be measured all three types of the linear chrominance distortions. As the results, the proposed gain equalizer is also proved to be efficient in equalizing both the low gain and the high gain chrominance distortions without degrading its phase characteristics.
Keywords: Chrominance; Distortion (music); Adaptive equalizer; Advancements in PLL and VCO Technologies